Availability, consumer acceptance and safety of some dried traditional vegetables in Tamale, Ghana - Dari, L; Nenguwo, N; Sefa, V Afari (Journal of Postharvest Technology, 2018)
In Ghana especially Tamale, vegetables are part of many dishes prepared with indigenous or traditional vegetables such as pepper, okra, bra,  tomatoes and jute mallow. These traditional vegetables include pepper, okro, roselle, tomato and jute mallow are cultivated both on small scale for  home consumption and on commercial basis for the local market and on large scale for export in the fresh form. It is also undisputed fact that  vegetables are often not growth all year round since most agricultural productions are rain-fed. Drying of vegetables is one way vegetables are  preserved as it removes enough moisture which inhibits the growth of microorganisms such as bacteria, yeast and fungi by ensuring food safety and  security. This study sought to determine the availability, access and safety of dried indigenous vegetables on the market. Data was collected using  questionnaire for the socioeconomic data, proximate and microbiological analysis was carried out using the official standards and recommendations of  the Association of Official Analytical Chemists. Results indicate access of dried traditional vegetables on the market with different consumer  preferences. Proximate compositions and varying microbial loads for the different vegetables were also established. Vegetables need to be sanitised  adequately and drying methods improved to ensure the elimination of microbial loads on dried vegetables for food safety and security.
Keywords: Consumer acceptance; microbial quality; sun dried; traditional; vegetables